The Role of Islamic Religious Education in Preventing Bullying Among Adolescents - Putri Latifah; Rosdialena (Journal Of Psychology, Counseling And Education, 2026)
Bullying is a social problem that is still frequently found among adolescents and can have detrimental impacts on the psychological condition, social relationships, and academic achievement of victims. This condition shows that bullying prevention is not sufficient only through the implementation of rules and sanctions in schools, but also needs to be supported by character and moral development of students. In this regard, Islamic Religious Education (PAI) plays a crucial role in instilling good moral values, such as mutual respect, compassion, tolerance, empathy, and responsibility towards others. These values ​​can serve as a foundation for adolescents to avoid bullying behavior. This study aims to examine the role of Islamic Religious Education in preventing bullying among adolescents. The method used is library research by reviewing various sources, such as books, scientific journals, and other literature relevant to Islamic Religious Education and bullying. The results show that Islamic Religious Education plays a role in bullying prevention through strengthening faith values, building Islamic character, moral education, and habituating positive behavior in daily life. Furthermore, collaboration between teachers, families, and the school community contributes to the effectiveness of Islamic Religious Education (PAI) in shaping positive adolescent behavior. Therefore, Islamic Religious Education can be an effective tool for creating a safe, comfortable, and bullying-free educational environment.